A method for improving the fast charging performance of niobium pentoxide by aluminum doping, and its products and applications

By doping aluminum into niobium pentoxide material to form aluminum-doped niobium pentoxide nanoparticles, the problems of low conductivity and unstable structure during fast charging and discharge are solved, and high-magnification and long-life battery applications are achieved.

CN115172735BActive Publication Date: 2025-04-22WUHAN UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210884233.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-25
Publication Date
2025-04-22
Estimated Expiration
2042-07-25

AI Technical Summary

Technical Problem

The existing niobium pentoxide (Nb2O5) materials have low conductivity and unstable structure during fast charging and discharging, limiting their high magnification and long-life battery applications.

Method used

By doping aluminum during the preparation of niobium pentoxide, aluminum-doped niobium pentoxide nanoparticles are formed and embedded in the nitrogen-doped carbon matrix framework to improve its conductivity and structural stability.

Benefits of technology

The rate performance and cyclic properties of niobium pentoxide material are significantly improved, so that it can exhibit long-term and stable electrochemical properties under high current density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115172735B_ABST
    Figure CN115172735B_ABST
Patent Text Reader

Abstract

The present invention proposes a method for improving the fast charging performance of niobium pentoxide by aluminum doping, that is, combining simple solvent thermal and heat treatment processes, introducing a certain amount of O 2‑ Vacancies and low oxidation state Nb 4+ , a modified niobium pentoxide material with stable fast charging performance was prepared, which improved the ionic conductivity and electrical conductivity. Due to the substitution of aluminum ions for niobium ions, the lattice stability of niobium pentoxide was improved, the undesirable transition of niobium ions in the battery cycle was reduced, the capacity during fast charging was stabilized, and the fast charging cycle stability was improved. When the modified niobium pentoxide material is used as the negative electrode of a lithium-ion battery, the niobium pentoxide material has a stable fast charging performance at 20A g ‑1 At a high current density of , the reversible specific capacity of 82 mAh g-1 can still be maintained after 9900 cycles, demonstrating long-term stability during high-rate charge and discharge. The present invention provides a very promising method for developing fast-charging electrode materials with high capacity and high structural stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion batteries, and specifically relates to a method for improving the fast-charging performance of niobium pentoxide by aluminum doping, and a product and application thereof. Background Art

[0002] As one of the important representatives of energy storage devices, lithium-ion batteries have attracted widespread attention due to their high energy density and long service life. As one of the key requirements for the next generation of lithium-ion batteries, fast charging has led to the development of high-rate electrode materials. Currently, carbon-based materials such as graphite (theoretical specific capacity of 372 mAh g -1 ) is a commonly used negative electrode material for lithium-ion batteries. However, graphite has limited rate performance and large initial capacity loss, which is far from meeting the requirements of high-rate and high-energy density devices. Other insertion materials such as Li4Ti5O 12 It has good safety performance, but its theoretical specific capacity (140 mAh g -1 ) greatly limits the output energy density of the battery. Therefore, the development of high-rate electrode materials with high capacity and excellent structural stability is of great significance for the development of long-life fast-charging chemical devices.

[0003] In recent years, niobium pentoxide (Nb2O5) has attracted attention due to its ultrafast lithium storage kinetics and has become a highly promising negative electrode material for the development of high-rate lithium-ion batteries. Among Nb2O5 with different crystal forms, orthorhombic niobium pentoxide (T-Nb2O5) has been widely studied as an intercalation pseudocapacitive material. Its structure is mainly composed of highly distorted octahedral (NbO6) and pentagonal bipyramidal (NbO7) skeletons. This open framework structure provides a stable host and high-speed channel for ion transport, thereby realizing high-rate energy storage of micron-sized particles. In addition, the intercalation pseudocapacitive behavior exhibited by T-Nb2O5 is conducive to the improvement of rate performance. However, the low conductivity of T-Nb2O5 (3×10 at 300K) -6 S cm -1 ) and instability at low cut-off voltages greatly limit its charge-discharge capacity and high-rate performance. Therefore, it is necessary to develop a simple method to improve the comprehensive performance of T-Nb2O5 during fast charge and discharge and give full play to its fast charging potential. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for improving the fast charging performance of niobium pentoxide by aluminum doping in view of the shortcomings of the above-mentioned prior art, thereby improving the electrical conductivity and structural stability of niobium pentoxide, thereby achieving the purpose of comprehensively improving the rate performance and cycle performance.

[0005] The technical solution adopted by the present invention to solve the above-mentioned problems is:

[0006] A method for improving the fast charging performance of niobium pentoxide by aluminum doping, wherein aluminum is doped during the preparation process of niobium pentoxide to improve the fast charging performance of niobium pentoxide, and specifically comprises the following steps:

[0007] 1) Mixing appropriate amounts of niobium source, aluminum source and organic ligand in an organic solvent;

[0008] 2) subjecting the mixed solution obtained in step 1) to a solvothermal reaction, and separating a solid product after the reaction is completed;

[0009] 3) heat-treating the solid product obtained in step 2) to obtain a modified niobium pentoxide material with fast charging performance.

[0010] According to the above scheme, in step 1), the niobium source used is selected from niobium pentachloride, niobium ethoxide, etc., the aluminum source is selected from aluminum nitrate nonahydrate, aluminum acetylacetonate, etc., the organic ligand is dimethylimidazole, etc., and the organic solvent is ethanol.

[0011] According to the above scheme, in step 1), the molar ratio of Al:Nb in the aluminum source and the niobium source is 1:50-1:20, the molar ratio of the niobium source to the organic ligand is 1:10-1:15, and the total concentration of the niobium source, the aluminum source and the organic ligand in the organic solvent is 0.02-0.04 g / mL.

[0012] According to the above scheme, in step 2), the solvent thermal reaction needs to be maintained at a temperature of 180-200° C. for 12-24 hours.

[0013] According to the above scheme, in step 3), the heat treatment needs to be carried out in a high-temperature tubular furnace, and the sintering atmosphere adopted is a hydrogen-argon mixed gas (the volume ratio of hydrogen to argon is generally between 3% / 97% and 5% / 95%). The heat treatment method is to increase the temperature to 750-850°C at 2-5°C / min and keep it warm for 2-5h, and then take it out after naturally cooling to room temperature.

[0014] The modified niobium pentoxide material with stable fast charging performance obtained by the above method is a micron sphere with a diameter of 0.5 to 3 μm, which is formed by dense stacking of aluminum-doped niobium pentoxide nanoparticles and nitrogen-doped carbon matrix skeleton.

[0015] The modified niobium pentoxide material with stable fast charging performance is used as a negative electrode material for lithium-ion batteries, which can achieve high current density (2A g -1 ~20A g -1 ) for rapid and stable lithium storage.

[0016] The present invention designs a method for improving the fast charging performance of niobium pentoxide. The metal ions are coordinated with the organic ligands in a solvent thermal process, and then calcined in a reducing atmosphere, so that the aluminum ions partially replace the niobium ions in the niobium pentoxide matrix, forming aluminum-doped niobium pentoxide nanoparticles embedded in the nitrogen-doped carbon matrix skeleton; aluminum doping and reducing atmosphere treatment introduce a certain amount of O 2- Vacancies and low oxidation state Nb 4+ , which improves the ionic conductivity and electrical conductivity; the substitution of aluminum ions for niobium ions improves the lattice stability of niobium pentoxide, reduces the adverse transitions of niobium ions in the battery cycle, stabilizes the capacity during fast charging, and improves the cycle stability of fast charging.

[0017] Compared with the prior art, the invention has the following beneficial effects: a modified niobium pentoxide material with stable and fast charging performance is prepared by a simple solvent thermal reaction and a heat treatment process under a reducing atmosphere, and its structural stability and conductivity are improved by aluminum doping, so that it exhibits excellent electrochemical performance at high charge and discharge rates. When the modified niobium pentoxide material with stable and fast charging performance is used as the negative electrode material of a lithium-ion battery, the modified niobium pentoxide material has a stable and fast charging performance at 0.1A g -1 At a current density of 430 mAh g -1 The reversible specific capacity at 20A g -1 At a high current density of 1.5 MW, it can still maintain 82 mAh g after 9900 cycles. -1 The reversible specific capacity shows long-term stability during high-rate charge and discharge. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The XRD pattern (a), TEM pattern (b-c) and EELS mapping pattern (d) of the modified niobium pentoxide material with fast charging performance prepared in Example 1;

[0019] Figure 2 The EDS element distribution diagram (a) and the EDS spectrum (b) of the corresponding area of ​​the modified niobium pentoxide material with fast charging performance prepared in Example 1;

[0020] Figure 3 is an atomic-level EDS element distribution diagram of a cross section of a modified niobium pentoxide material with fast charging performance prepared in Example 1;

[0021] Figure 4 High-resolution XPS spectra of (a) Al 2p, (b) O1s and (c) Nb 3d of the modified niobium pentoxide material with fast charging performance prepared in Example 1.

[0022] Figure 5The cyclic voltammetry curves of the first three cycles of Al-Nb2O5@NC (a) prepared in Example 1 and Nb2O5@NC (b) prepared in Comparative Example 1 are shown in Figure 1, with a scan rate of 0.2 mV s -1 , the scanning range is 0.01~3V;

[0023] Figure 6 The electrochemical performance diagrams in the voltage range of 0.01 to 3 V are as follows: (a) shows the electrochemical performance of Al-Nb2O5@NC prepared in Example 1 and Nb2O5@NC prepared in Comparative Example 1 at 0.1 A g -1 (b) shows the cycling performance comparison of Al-Nb2O5@NC prepared in Example 1 and Nb2O5@NC prepared in Comparative Example 1 at 0.1A g -1 to 2A g -1 (c) and (d) are the rate performance of Al-Nb2O5@NC prepared in Example 1 and Nb2O5@NC prepared in Comparative Example 1 at 2A g -1 and 20A g -1 Comparison of long cycle performance under high current density.

[0024] Figure 7 The ex-situ STEM images after cycling in a half-cell. (a) HAADF-STEM image of the initial state of Al-Nb2O5@NC prepared in Example 1 along the

[100] direction. (b) HAADF-STEM image of the initial state of Al-Nb2O5@NC prepared in Example 1 along the [5-10] direction in 2Ag -1 (c) HAADF-STEM image of the initial state of Nb2O5@NC prepared in Comparative Example 1 along the [8-10] direction. (d) HAADF-STEM image of the initial state of Nb2O5@NC prepared in Comparative Example 1 at 2A g -1 HAADF-STEM image after 300 cycles at a current density of . DETAILED DESCRIPTION

[0025] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.

[0026] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0027] Unless otherwise specified, all reagents and raw materials used in the present invention are commercially available products or products that can be prepared by known methods.

[0028] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0029] Comparative Example 1

[0030] A method for preparing niobium pentoxide / nitrogen-doped carbon microspheres, comprising the following steps:

[0031] 1) Add 0.27 g of niobium pentachloride and 0.82 g of dimethylimidazole to 35 ml of ethanol and stir for 30 minutes to obtain a clear mixed solution;

[0032] 2) reacting the clarified mixed solution obtained in step 1) at 200° C. for 24 h, taking it out after the reaction and naturally cooling it to room temperature, centrifuging and washing it, and then drying it in an oven at 70° C. for 12 h;

[0033] 3) The dried product obtained in step 2) is placed in a high-temperature tube furnace, and kept at 800°C for 2 hours in a hydrogen-argon mixed atmosphere (5% / 95%), with a heating rate of 5°C / min. After naturally cooling to room temperature, the dried product is taken out, and the obtained product is niobium pentoxide / nitrogen-doped carbon microspheres (Nb2O5@NC).

[0034] Example 1

[0035] A method for improving the fast charging performance of niobium pentoxide by aluminum doping, wherein aluminum is doped during the preparation process of niobium pentoxide to improve the fast charging performance of niobium pentoxide, and specifically comprises the following steps:

[0036] 1) 0.27 g of niobium pentachloride, 0.015 g of aluminum nitrate nonahydrate and 0.82 g of dimethylimidazole were added to 35 ml of ethanol and stirred for 30 minutes to obtain a clear mixed solution;

[0037] 2) reacting the mixed solution obtained in step 1) at 200° C. for 24 h, taking it out after the reaction and naturally cooling it to room temperature, centrifuging and washing it, and then drying it in an oven at 70° C. for 12 h;

[0038] 3) The dried product obtained in step 2) is placed in a high-temperature tube furnace, and kept at 800°C for 2 hours in a hydrogen-argon mixed atmosphere (5% / 95%), with a heating rate of 5°C / min. After naturally cooling to room temperature, the product is taken out, and the obtained product is a modified niobium pentoxide material with fast charging performance, which is an aluminum-doped niobium pentoxide / nitrogen-doped carbon microsphere (Al-Nb2O5@NC).

[0039] The product of this example, aluminum-doped niobium pentoxide / nitrogen-doped carbon microspheres (Al-Nb2O5@NC), was characterized in terms of morphology and structure. Figure 1As shown in a, the XRD spectrum shows that the product is a pure, highly crystalline orthorhombic phase Al-Nb2O5@NC. TEM image ( Figure 1 b) shows that Al-Nb2O5@NC is a microsphere with a diameter of 0.5 to 3 μm. The microsphere was sliced ​​by focused ion beam (FIB) to obtain a thin cross section, TEM and EELS mapping of the cross section ( Figure 1 cd) show that the microspheres are stacked by aluminum-doped niobium pentoxide nanoparticles and nitrogen-doped carbon matrix skeleton.

[0040] Figure 2 In the EDS element distribution diagram ( Figure 2 a) shows the distribution of Al, Nb, O, C, and N elements in Al-Nb2O5@NC microspheres, and the EDS spectrum of the corresponding area ( Figure 2 b) Clear peaks corresponding to Al, C, and N verify the presence of nitrogen-doped carbon in the microspheres and the successful incorporation of aluminum.

[0041] Figure 3 This is the atomic-level EDS image of Al-Nb2O5@NC. It can be seen that the Al and Nb elements are distributed in the atomic layer, which means that the aluminum atoms partially replace the niobium atoms in the lattice.

[0042] Figure 4 High-resolution XPS spectra of (a) Al 2p, (b) O1s and (c) Nb 3d of Al-Nb2O5@NC. It can be seen that Al doping and reducing atmosphere treatment lead to the 5+ and Nb 4+ coexistence and the introduction of oxygen vacancies promotes the Li + diffusion and electron transport.

[0043] The electrochemical performance test of the Al-Nb2O5@NC material prepared in this embodiment and the Nb2O5@NC material prepared in comparative example 1 was conducted by assembling half-cells using button cells. The active material (the active material is the Al-Nb2O5@NC material prepared in this embodiment or the Nb2O5@NC material in comparative example 1), acetylene black, and polyvinylidene fluoride are prepared into an electrode slurry in a mass ratio of 7:2:1, coated on a copper foil, and dried to obtain an electrode sheet. A metal lithium sheet is used as the counter electrode, and the assembly is carried out in a glove box filled with argon. Cyclic voltammetry test ( Figure 5 (ab)) show that Al-Nb2O5@NC and Nb2O5@NC have similar CV curves, indicating that they have similar redox reactions; but Al-Nb2O5@NC exhibits a larger peak current and a smaller redox potential difference, which indicates that the Al-Nb2O5@NC electrode has a higher specific capacity and a relatively lower polarizability.

[0044] The Al-Nb2O5@NC prepared in this embodiment and the Nb2O5@NC prepared in comparative example 1 were subjected to charge and discharge tests: Figure 6 As shown in a, compared with Nb2O5@NC, Al-Nb2O5@NC -1 It has lower initial capacity loss and higher reversible specific capacity (~430 mAh g -1 ).like Figure 6 As shown in b, Al-Nb2O5@NC exhibits better rate performance. When the current density increases from 0.1A g-1 to 2A g-1, -1 When the specific capacity is still stable at 230mAh g -1 When the current density is reduced to 0.1A g-1, the discharge capacity can be restored to 440.7mAh g -1 Comparison of cycling performance at high current density Figure 6 As shown in (c, d), the specific capacity of Al-Nb2O5@NC is 2A g -1 After 2500 cycles, it can maintain 267mAh g -1 , at 20A g -1 After 9900 cycles, it can maintain 82mAh g -1 , which is better than Nb2O5@NC. These results show the stable fast charging capability of Al-Nb2O5@NC and confirm that Al doping provides a significant improvement in the lithium storage performance of Nb2O5.

[0045] Ex situ STEM analysis was performed on the Al-Nb2O5@NC prepared in this example and the Nb2O5@NC prepared in Comparative Example 1. Figure 7 As shown in (a, b), the migration of Nb ions was found in the Al-Nb2O5@NC sample after long cycles. The migration of Nb (from Nb1-Nb4 to Nb5-Nb7) partially occupied the cation vacancies in the original structure, which not only reduced the capacity but also aggravated the rapid diffusion of lithium ions during the cycle. Compared with before the cycle, the crystallinity of the material decreased, but its main structure remained unchanged. In contrast, the situation of Nb2O5@NC was worse, with severe Nb migration, defects and grain boundaries, which caused the crystals to shatter ( Figure 7 (c, d)). Therefore, during the fast lithium deintercalation / intercalation process, Al-Nb2O5@NC reduces the migration degree of Nb due to Al doping, stabilizes the capacity during fast charging, and improves the cycling stability of fast charging.

[0046] Example 2

[0047] A method for improving the fast charging performance of niobium pentoxide by aluminum doping, wherein aluminum is doped during the preparation process of niobium pentoxide to improve the fast charging performance of niobium pentoxide, and specifically comprises the following steps:

[0048] 1) 0.27 g of niobium pentachloride, 0.0075 g of aluminum nitrate nonahydrate and 0.82 g of dimethylimidazole were added to 35 ml of ethanol and stirred for 30 minutes to obtain a clear mixed solution.

[0049] 2) The mixed solution obtained in step 1) was reacted at 200° C. for 24 h, and after the reaction, it was taken out and naturally cooled to room temperature, centrifuged and washed, and then placed in a 70° C. oven to dry for 12 h.

[0050] 3) The dried product obtained in step 2) is placed in a high-temperature tube furnace, and kept at 800°C for 2 hours in a hydrogen-argon mixed atmosphere (5% / 95%), with a heating rate of 5°C / min. After naturally cooling to room temperature, the product is taken out, and the obtained product is a modified niobium pentoxide material with fast charging performance.

[0051] Example 3

[0052] A method for improving the fast charging performance of niobium pentoxide by aluminum doping, wherein aluminum is doped during the preparation process of niobium pentoxide to improve the fast charging performance of niobium pentoxide, and specifically comprises the following steps:

[0053] 1) 0.27 g of niobium pentachloride, 0.0187 g of aluminum nitrate nonahydrate and 0.82 g of dimethylimidazole were added to 35 ml of ethanol and stirred for 30 minutes to obtain a clear mixed solution.

[0054] 2) The mixed solution obtained in step 1) was reacted at 200° C. for 24 h, and after the reaction, it was taken out and naturally cooled to room temperature, centrifuged and washed, and then placed in a 70° C. oven to dry for 12 h.

[0055] 3) The dried product obtained in step 2) is placed in a high-temperature tube furnace, and kept at 800°C for 2 hours in a hydrogen-argon mixed atmosphere (5% / 95%), with a heating rate of 5°C / min. After naturally cooling to room temperature, the product is taken out, and the obtained product is a modified niobium pentoxide material with fast charging performance.

[0056] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and changes without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for improving the fast charging performance of niobium pentoxide by aluminum doping, characterized in that: By doping aluminum in the preparation process of niobium pentoxide, the fast charging performance of niobium pentoxide is improved, which specifically includes the following steps: 1) Mixing appropriate amounts of niobium source, aluminum source and organic ligand in an organic solvent to obtain a mixed solution; 2) subjecting the mixed solution obtained in step 1) to a solvothermal reaction to separate a solid product; wherein the niobium source is niobium pentachloride, the organic ligand is dimethylimidazole, and the organic solvent is ethanol; 3) calcining the solid product obtained in step 2) under a reducing atmosphere, wherein the reducing atmosphere is a hydrogen-argon mixed gas, and the volume ratio of hydrogen to argon is between 3% / 97% and 5% / 95%, to obtain a modified niobium pentoxide material with stable fast charging performance; The modified niobium pentoxide material with stable fast charging performance is a micron sphere with a diameter of 0.5-3 µm, which is formed by dense stacking of aluminum-doped niobium pentoxide nanoparticles and nitrogen-doped carbon matrix skeleton.

2. The method according to claim 1, characterized in that: In step 1), the aluminum source is selected from one or both of aluminum nitrate nonahydrate and aluminum acetylacetonate.

3. The method according to claim 1, characterized in that: In step 1), the molar ratio of Al:Nb in the aluminum source and the niobium source is 1:50-1:20, the molar ratio of the niobium source to the organic ligand is 1:10-1:15, and the total concentration of the niobium source, the aluminum source and the organic ligand in the organic solvent is 0.02-0.04 g / mL.

4. The method according to claim 1, characterized in that: In step 2), the solvothermal reaction is maintained at 180-200°C for 12-24 h.

5. The method according to claim 1, characterized in that: In the step 3), the heat treatment is carried out in a high temperature tube furnace, and the heat treatment method is to increase the temperature to 750-850°C at 2-5°C / min and keep the temperature for 2-5 hours, and then take out after naturally cooling to room temperature.

6. The modified niobium pentoxide material with stable fast charging performance obtained by any one of the methods of claims 1 to 5 is used as a negative electrode material for lithium-ion batteries.

7. The use according to claim 6, characterized in that: When the modified niobium pentoxide material is used as the negative electrode material, the lithium-ion battery can be used at a high current density of 2 A g -1 ~20 A g -1 Rapid and stable lithium storage is achieved.

Citation Information

Patent Citations

  • Synthesizing method of modified columbic anhydride for lithium ion battery

    CN102593441A